2014
DOI: 10.3109/15622975.2014.966145
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic theta activity and cognition in schizophrenia: Preliminary results

Abstract: These preliminary results suggest that electroencephalographic resting state theta power is an indicator of cognitive deficit in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This finding is consistent with previous research implicating theta-band oscillations in neurocognitive deficits (Wichniak et al, 2014) or cognitive fatigue (Barwick et al, 2012) in general, and in mnemonic operations in particular: Successful memory encoding has been associated with changes in theta-band oscillatory power along a specific time course (Guderian et al, 2009;Long et al, 2014;Osipova et al, 2006;Sederberg et al, 2006), and theta-band oscillations are sensitive to factors affecting memory performance such as processing depth, contextual manipulations and cognitive load (Guderian et al, 2009;Hanslmayr and Staudigl, 2014;Sederberg et al, 2006). Moreover, it has been suggested that mnemonic operations might be dependent on precise modulations of theta-band synchronization within widely distributed brain networks (Burke et al, 2013;Fell and Axmacher, 2011;Sato and Yamaguchi, 2007;Summerfield and Mangels, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with previous research implicating theta-band oscillations in neurocognitive deficits (Wichniak et al, 2014) or cognitive fatigue (Barwick et al, 2012) in general, and in mnemonic operations in particular: Successful memory encoding has been associated with changes in theta-band oscillatory power along a specific time course (Guderian et al, 2009;Long et al, 2014;Osipova et al, 2006;Sederberg et al, 2006), and theta-band oscillations are sensitive to factors affecting memory performance such as processing depth, contextual manipulations and cognitive load (Guderian et al, 2009;Hanslmayr and Staudigl, 2014;Sederberg et al, 2006). Moreover, it has been suggested that mnemonic operations might be dependent on precise modulations of theta-band synchronization within widely distributed brain networks (Burke et al, 2013;Fell and Axmacher, 2011;Sato and Yamaguchi, 2007;Summerfield and Mangels, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…Under physiological conditions the relative spectral power of theta waves is representative of the “on-line” state of the hippocampus or learning and memory 31 , 32 . Studies from other neurological diseases such as schizophrenia and Alzheimer’s disease indicate a strong positive correlation between cognitive impairment and high theta power 33 , 34 . The higher theta power that we observed in the cortical and hippocampal recordings from AS mice is seen in parallel with deficits in spatial learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…A high number of studies focused on the association between theta activity and cognitive deficits. In SCZ three studies found significant negative correlations (increased EEG activity—worse cognitive performance) between theta power recorded at rest with cognitive functions, such as visuospatial memory [ 107 ], working memory [ 86 ], verbal learning [ 86 , 107 ], executive functioning [ 107 ] and emotion recognition [ 85 ]. In addition, theta band connectivity during resting state was a significant predictor of deficits in lexical processing [ 101 ] and verbal memory [ 92 ] in FES and CHR subjects and was also associated with deficits in the ability to initiate a consistent and coherent cognitive activity during a verbal fluency test in FES [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within the slow activity range, the band most robustly associated with cognitive deficits was theta, probably due to its role in the coordination of neural activity of the default-mode network, which is highly involved in automated processing of information [ 89 , 272 ], effortful cognitive processing and efficient allocation of attentive resources [ 98 , 102 , 107 ]. Furthermore, relationships between alterations in connectivity and measures of verbal memory and speed of processing suggest a possible role of disturbed communication across cortical areas and aberrant temporal synchronization of neuronal oscillators in the genesis of cognitive dysfunctions in schizophrenia [ 92 , 94 , 95 , 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%